Hydrogen-Bonding Interactions in Luminescent Quinoline-Triazoles with Dominant 1D Crystals - Shi-Qiang Bai; David James Young; T. S. Andy Hor (Molecules, 2017)
Quinoline-triazoles 2-((4-(diethoxymethyl)-1H-1,2,3-triazol-1-yl)methyl)quinoline (1), 2-((4-(m-tolyl)-1H-1,2,3-triazol-1-yl)methyl)quinoline (2) and 2-((4-(p-tolyl)-1H-1,2,3-triazol-1-yl)methyl)quinoline (3) have been prepared with CuAAC click reactions and used as a model series to probe the relationship between lattice H-bonding interaction and crystal direction of growth. Crystals of 1–3 are 1D tape and prism shapes that correlate with their intermolecular and solvent 1D lattice H-bonding interactions. All compounds were thermally stable up to about 200 C and blue-green emissive in solution.